2021
DOI: 10.1556/204.2020.00024
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of European bailout arrangements and its impact on sovereign bond yields in the aftermath of the euro crisis

Abstract: The 2010–2012 euro crisis prompted a wave of institutional reforms in the European Economic and Monetary Union (EMU), and one of the most remarkable changes was the creation of a permanent bailout facility for troubled sovereigns. The birth of the European Stability Mechanism (ESM) in 2012 was preceded by harsh debates, reflecting a conflict between a German view of country-level responsibility and French-Italian calls for more risk sharing. These tensions have remained ever since, which was also highlighted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Boros and Sztanó found that announcements of bailout framework by the EMU caused a further deterioration of bond yields in the troubled nations, leading to a spiralling of the negative effects of the crisis (2021). The announcements of the EMU's responses "significantly decreased government bond yields in the eurozone periphery" (Boros & Sztanó, 2021). In a self-fulfilling way, investors pushing up bond yields led to even weaker economic conditions; ultimately requiring stricter austerity and bailout measures and further worsening their returns.…”
Section: Section Two -Response and Criticismsmentioning
confidence: 99%
“…Boros and Sztanó found that announcements of bailout framework by the EMU caused a further deterioration of bond yields in the troubled nations, leading to a spiralling of the negative effects of the crisis (2021). The announcements of the EMU's responses "significantly decreased government bond yields in the eurozone periphery" (Boros & Sztanó, 2021). In a self-fulfilling way, investors pushing up bond yields led to even weaker economic conditions; ultimately requiring stricter austerity and bailout measures and further worsening their returns.…”
Section: Section Two -Response and Criticismsmentioning
confidence: 99%